The Judicial Duty to Give Reasons: Thong Ah Fat v Public Prosecutor [2011] SGCA 65 - CHEN, Siyuan (Institutional Knowledge at Singapore Management University, 2011)
The accused was charged under the Misuse of Drugs Act after being found with 142.41 grams of diamorphine at the Woodlands Checkpoint. The High Court Judge found the accused guilty and sentenced him to death in a brief judgment of five paragraphs. The Court of Appeal, however, ordered a retrial as it was of the view that the Judge’s reasoning was “unclear” and the “judicial duty to give reasoned decisions” was not discharged